PENGARUH MOTIVASI DAN MODAL MINIMAL TERHADAP MINAT INVESTASI SAHAM MAHASISWA DI BATAM - Saputra, Evan Zestya; Purba, Daris (LPPM Universitas Putera Batam, 2021)
Investment is an accumulation of a certain amount of capital with the aim of getting a numberof benefits at a later date. Capital can be in the form of money or other resources. Thepurpose of this research was to determine the effect of motivation and minimum capital onthe interest on investing in stock on college student in Batam, both partially andsimultaneously. The population in this research were all students studying at a university orcollege in Batam and the sample was Batam college student who had studied capitalmarkets or finance. Collecting data in this research using a questionnaire. The data analysismethod used in this research is multiple linear regression analysis with hypothesis testingusing the t test and F test on the SPSS 26 application. The results of this research are,partially motivation has a significant effect on the interest on investing in stock on collegestudent in Batam, while minimum capital partially has no significant effect on the interest oninvesting in stock on college student in Batam. Simultaneously, motivation and minimalcapital have a significant effect on the interest on investing in stock on college student inBatam.